Ion imprinted adsorbent for the removal of Ni(II) from waste water: preparation, characterization, and adsorption. Issue 12 (2nd December 2019) - Zhang, Yong; Bai, Zhishan; Luo, Wenqiang; Zhai, Linlin; Wang, Bingjie; Kang, Xiaohu; Zong, Jieqiong
Abstract: In this paper, a selective nickel ions chelating adsorbents (Ni-CMCS) were prepared based on carboxymethyl chitosan by ion imprinting technique. Scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS) were used to investigate their physicochemical properties. Brunauer-Emmett-Teller (BET) analysis showed that the BET surface area of Ni-CMCS had a significant increase after ion imprinting process. The effects of pH value, contact time and initial concentration of Ni(II) were studied. The adsorption kinetics were investigated, which indicated that Ni-CMCS was better fitted with pseudo-second-order kinetic model (R 2 = 0.9991) with film diffusion process as rate controlling step. The adsorption isotherms study indicated that Langmuir model matched better with the experimental data for Ni-CMCS (R 2 = 0.9617). Besides, the maximum adsorption capacity calculated from the Langmuir equation was 82.78 mg g −1 . Moreover, the selectivity experiment suggested that Ni-CMCS had good selectivity in the presence of Co(II), Mn(II), or Cd(II). After used four cycles, Ni-CMCS kept great adsorption capacity. Graphical Abstract: UF0001